Strategi Learning Start with a Question dengan Media Video Animasi terhadap Literasi Membaca Peserta Didik Kelas V di SDIT Al Ghifari - Suliyantini; Lestari, Hana; Ihsan, Muzir (Primer Edukasi Journal, 2024)
This study aims to determine whether there is an effect of implementing the learning start with a question strategy with animated video media on students' reading literacy. The subjects of this study were class V-B and C of the Al GHIFARI Integrated Islamic Elementary School (SDIT) totaling 59 students who were divided into two experimental and control groups. The method used is a quasy experiment with a pre-post test two control group design. The instruments used were reading literacy tests, observations and interviews. The reading literacy test is divided into two stages, namely pretest and posttest. The results of the reading literacy test in this study obtained an average pretest score of 16.5 for the experimental class and an average score for the posttest of the experimental class was 25.74. Meanwhile, the pretest score for the control class was 15.83 and the posttest average score was 18.97. Data management uses SPPS 24 For Windows with two t-tests, namely the Paired sample t-test and the Independent sample t-test at ɑ (0.05) and the acquisition of a sig value of 0.000 < ɑ (0.05). The results of the study showed that there were significant differences between the pretest and posttest of the experimental and control classes. Furthermore, the experimental class n-gain value was 0.558 (moderate category) while the control class obtained a value of 0.216 (low category). It can be interpreted that there is an influence on the implementation of the learning start with a question strategy with animated video media for the experimental class.